Studi Termodinamika Adsorpsi Pb(II) Menggunakan Adsorben Magnetik GO-Fe3O4 yang Disintesis dari Kayu Kusambi (Schleichera oleosa) - Yantus A B Neolaka; Yosep Lawa; Johnson N Naat; Yohana K Nubatonis; Arsel A. Pau Riwu (Fakultas Pertanian, Universitas Timor, 2019)
The study on the adsorption of Pb(II) using magnetic adsorbent GO-Fe3O4 that synthesized from kusambi wood (Schleichera oleosa) in the bacth system will be reported. Here, two adsorption parameters such as initial concentration and adsorption thermodynamics were thoroughly studied. The results showed that the initial concentration of the best adsorption of Pb(II) using magnetic adsorbent GO-Fe3O4 from kusambi wood (Schleichera oleosa) lasted a maximum between concentrations of 10 mg/L to 40 mg/L. In addition, based on thermodynamic studies, it is known that the adsorption of Pb(II) on the surface of GO-Fe3O4 from kusambi wood (Schleichera oleosa) has follows physisorption mechanism. Overall, this study indicates that GO-Fe3O4 magnetic material from kusambi wood (Schleichera oleosa) can be used to adsorb Pb(II) from the aquatic environment.